Older people and death-thought accessibility: The association between death and older people in memory. - Boudjemadi, Valérian; Posner, Alexandra; Bastart, Jennifer (Death Studies, 2022)
This work aimed to conceptually replicate and extend Martens, Greenberg, Schimel, and Landau's findings about older people as threatening future self. We conducted two studies using a lexical decision task to measure death-thought accessibility. Results showed that older people primes lead to stronger facilitation of death-related compared, with negative words. Such a facilitation is not observed with young people primes (Study 1). Moreover, the automatic association between the representation of older people and death was stronger when participants and older people primes were of the same sex (Study 2). Implications of these findings with respect to ageism are discussed.